Pre-trial Procedures in Administrative Justice Proceedings in England and Wales, France, Germany and the Netherlands : A Comparative Study with a View to the Possible Development of Pre Trial Procedures in Administrative Law in Turkey - World Bank (World Bank, 2012)
Disputes between citizens or businesses and the State about respective rights and duties are at the core of administrative law. The ability for citizens and businesses to hold Government accountable for acting within the rule of law is a key element of good governance. It provides legal certainty and guarantees predictable and rule-based implementation of legal and regulatory frameworks across different sectors. It also provides Government with effective mechanisms to enforce these frameworks. An effective administrative justice system is therefore a crucial element to make sure all players follow the rules of the game. As such, it is an important aspect of a sound investment climate. The Turkish Ministry of Justice has identified the absence of pre-trial procedures in the administrative justice system as a major obstacle to the efficient and effective delivery of judicial services to citizens, businesses, and the state. There are widespread complaints that administrative judges crumble after a heavy workload and that certain types of cases may be more effectively dealt with outside of the courts. This will make dispute resolution for citizens, businesses, and the state more effective and will alleviate the workload of the administrative courts. Current dysfunctions also affect Turkey's ability to live up to its commitments under the European convention for human rights. Its article six grants those seeking justice the right to a fair trial within reasonable time. Citizens and businesses bring complaints to the European court of human rights which has the power to condemn signatory states for non-compliance. This has financial implications as a country found in violation of this convention has to pay compensation. Beyond the financial implications, though, it negatively affects the image of the Turkish justice system abroad and particularly in Europe, which casts a cloud over European Union accession negotiations.